Effect of Die Head Temperature at Compounding Stage on the Degradation of Linear Low Density Polyethylene/Plastic Film Waste Blends after Accelerated Weathering - S. M. Al-Salem; N. M. Al-Dousari; G. Joseph Abraham; M. Aromin D’Souza; O. A. Al-Qabandi; W. Al-Zakri (International Journal of Polymer Science)
Accelerated weathering test was performed on blends of linear low density polyethylene (LLDPE) and plastic film waste constituting the following percentages of polyolefin polymers (wt.%): LLDPE (46%), low density polyethylene (LDPE, 51%), high density polyethylene (HDPE, 1%), and polypropylene (PP, 2%). Compounded blends were evaluated for their mechanical and physical (optical) properties. The impact of photodegradation on the formulated blends was studied, and loss of mechanical integrity was apparent with respect to both the exposure duration to weathering and waste content. The effect of processing conditions, namely, the die head temperature (DHT) of the blown-film assembly used, was investigated in this work. It was witnessed that surpassing the melting point of the blends constituting polymers did not always result in a synergistic behaviour between polymers. This was suspected to be due to the loss of amorphous region that polyolefin polymers get subjected to with UV exposure under weathering conditions and the effect of the plastic waste constituents. The total change in colour (ΔE) did not change with respect to DHT or waste content due to rapid change degradation on the material’s surface. Haze (%) and light transmission (%) decreased with the increase in waste content which was attributed to lack of miscibility between constituting polymers.